(Re)making the Social World: The Politics of Transitional Justice in Burundi. Issue 1 (April 2013) - Rubli, Sandra
Focusing on political parties, this article highlights divergent conceptualizations of key elements of transitional justice that are part of the current contestation of the dealing-with-the-past process in Burundi. Speaking to the emerging critical literature on transitional justice, this article attempts to look beyond claims that there is a lack of political will to comply with a certain global transitional justice paradigm. In this article, transitional justice is conceived of as a political process of negotiated values and power relations that attempts to constitute the future based on lessons from the past. This paper argues that political parties in Burundi use transitional justice not only as a strategy to protect partisan interests or target political opponents, but also as an instrument to promote their political struggles in the course of moulding a new, post-conflict society and state.